Determinants of Human Development Index in Indonesia with Maqashid Sharia approach - Caniago, Muhammad Ali Imran; Wibowo, Muhammad Ghafur (ITB AAS INDONESIA Surakarta, 2024)
The study examines factors that influence the Indonesian Human Development Index using the Maqashid Sharia approach. This study's sample is made up of several provinces with the Human Development Index for different categories of people. Data analysis employs a panel data regression model with a fixed effect model. The study's findings indicate that whereas variables Hifzu al-din, Hifzu al-aql, and Hifzu al-mal have a significant impact on the Index of Human Development, variables Hifzu al-nafs and Hifzu al-nasl have no significant impact on the Index of Human Development. Simultaneously, the variables Hifzu al-din, Hifzu al-nafs, Hifzu al-aql, Hifzu al-nasl, and Hifzu al-mal exhibit significant effects on the Human Development Index. Results of the determination test show that 98% of independent variables can influence dependent variables, with the remaining 2% being affected by variables not examined in this study. The study's findings recommended to the government that they support Hifzu Al-din in reducing crime rates, Hifzu Al-Aql by increasing the average length of schooling, and Hifzu Al-Mal in raising per capita income. By paying more attention to these issues, human development will eventually reach its full potential.